The Addis Declaration on Immunization: Assessing the Effectiveness and Efficiency of Immunization Service Delivery Systems in Africa as of the End of 2023 - Franck Mboussou; Charles Shey Wiysonge; Bridget Farham; Ado Bwaka; Sarah Wanyoike; Amos Petu; Sidy Ndiaye; Andre Bita Fouda; Johnson Muluh Ticha; Adidja Amani; Regis Obiang; Magaran Monzon Bagayoko; et al. (Vaccines, 2024)
Background/Objectives: The Addis Declaration on Immunization (ADI) is a historic pledge aiming at increasing political will to achieve universal access to immunization services and includes ten commitments to shape the future of immunization in Africa. Methods: To analyze African countries’ performance in achieving the fourth ADI commitment, a cross-sectional retrospective study was conducted including the 54 African Member States of the World Health Organization (WHO) out of 55 African Union (AU) Member States. The fourth ADI commitment aims at increasing the effectiveness and efficiency of immunization delivery systems and has four performance indicators. Results: The median percentage of districts with less than 10% of dropout rate between the first dose of diphtheria–tetanus–pertussis-containing vaccine (DTP1) and the third dose (DTP3) was 86.5%, ranging from 22% to 100%. Thirty-four countries (63%) recorded 80% or above of districts with less than 10% dropout rate between DTP1 and DTP3. Eleven countries (20.3%) and ten countries (18.5%) sustained 90% or above coverage for DTP3 and first dose of measles-containing vaccine (MCV1), respectively, in the past three years (2021–2023). Four countries (7.4%) had 44.5 skilled health workers per 10,000 people. Out of the 54 WHO Member States, 7 achieved at least three of the four indicators of the fourth ADI commitment (13%). Conclusions: It is critical, as a follow up to this study, to document best practices from the seven countries that achieved the fourth ADI commitment. Additionally, a deeper analysis of factors associated with achieving the ADI commitments is required.